External validation of CLI Frailty Index and assessment of predictive value of modified CLI Frailty Index for patients with critical limb ischemia undergoing infrainguinal revascularization. (August 2019) - Morisaki, Koichi; Furuyama, Tadashi; Matsubara, Yutaka; Inoue, Kentaro; Kurose, Shun; Yoshino, Shinichiro; Nakayama, Ken; Yamashita, Sho; Yoshiya, Keiji; Yoshiga, Ryosuke; Maehara, Yoshihiko
Objectives: CLI Frailty is a useful diagnostic criterion of frailty in patients with critical limb ischemia (CLI). It is important to evaluate not only comorbidities but also frailty in decision making to select the type of treatment for CLI patients. The purposes of our study were to externally validate the CLI Frailty Index and to evaluate the modified CLI Frailty Index by measurement of skeletal muscle mass using computed tomography. Methods: Patients who underwent preoperative computed tomography examination and infrainguinal revascularization between 2002 and 2015 were retrospectively analyzed. A patient was defined as CLI Frailty (+), if two or more of the following criteria were present: low Geriatric Nutritional Risk Index (GNRI), low skeletal muscle mass index (SMI) evaluated by prediction equations, and non-ambulatory status. For the modified CLI Frailty Index, skeletal muscle area was measured by computed tomography instead of prediction equations. Results: During the study period, 226 patients with CLI underwent revascularization; we included 127 patients and excluded 99 patients who were treated only with iliac revascularization or did not undergo CT scans. The overall survival at two years after revascularization was 83.6% for the CLI Frailty (−) group versus 63.2% for the CLI Frailty (+) group ( P = .02). The overall survival at two years after revascularization was 89.7% for the modified CLI Frailty (−) group versus 60.5% for the modified CLI Frailty (+) group ( P < .01). Multivariate analysis 1 including CLI Frailty revealed that hemodialysis (HR, 3.71; 95% CI, 1.58–8.83; P < .01), CLI Frailty (HR, 3.22; 95% CI, 1.35–7.47; P < .01) and cerebrovascular disease (HR, 2.58; 95% CI, 1.09–5.91; P = .03) were risk factors for overall survival two years after revascularization. In multivariate analysis 2 including modified CLI Frailty, modified CLI Frailty (HR, 5.92; 95% CI, 2.49–15.7; P < .01), hemodialysis (HR, 4.03; 95% CI, 1.65–10.0; P < .01) and diabetes mellitus (HR, 0.41; 95% CI, 0.16–0.99; P = .05) were risk factors for overall survival two years after revascularization. Conclusions: Both the CLI Frailty and the modified CLI Frailty Indexes were useful in predicting the two-year overall survival of patients with CLI after infrainguinal revascularization. Although the measurement of skeletal muscle mass using computed tomography may accurately predict two-year overall survival, SMI prediction is effective for patients with CLI who did not undergo preoperative CT.